Local people's preferences for biodiversity offsets to achieve 'no net loss' for economic developments. (August 2019) - Griffiths, Victoria F.; Sheremet, Oleg; Hanley, Nick; Baker, Julia; Bull, Joseph W.; Milner-Gulland, E.J.
Abstract: Understanding people's preferences for biodiversity offsetting activities can help to design offsets that achieve 'no net loss' (NNL) of biodiversity while incorporating the use and cultural values associated with this biodiversity. We use a stated preference choice experiment to solicit preferences for different proposed biodiversity offsets, linked to two hydropower developments in Uganda, with the aim of improving social outcomes of the offsets. We surveyed 1215 respondents from six villages located along the river impacted by the hydropower projects. Overall, people preferred offsets and compensatory activities that benefit the entire village rather than just a few individuals. People opposed the removal of non-native trees from their Central Forest Reserve and some responded negatively towards free access to spiritual sites. Respondents' choices were influenced by gender, age, education level, length of time lived in the village, level of poverty, and whether they believed that the hydropower development had affected their wellbeing. Preferences also varied significantly between villages. Our findings provide insight into locally preferred options for biodiversity NNL offsets. They also demonstrate the use of choice experiments to inform decisions about biodiversity offsets, as part of ensuring that NNL strategies do not make local people worse off. Highlights: Choice experiments provide valuable insights into the design of biodiversity offsets. We show which social gains are most valued in a natural resource-dependent context. Activities benefitting the village are preferred to those benefitting individuals. Preferences for offsets vary geographically between villages. Preferences should be accounted for in designing sustainable biodiversity actions.